Metal pollutation in the aquatic environmental - Forstner, U | Wittman, G.T.W (Springer-Verlag / New York, 1983)
Contents: Environmental pollution; Toxic metals; Metal concentrations in river; Lake and ocean waters; Metal pollution assessment from sediments analysis; Metal transfer between solid and aqueous phases